The Cylapinae (Insecta, Hemiptera, Heteroptera: Miridae) of India: review of the subfamily with description of new species - Yeshwanth, H. M.; Chérot, F.; Gorczyca, J.; Wolski, A. (Zootaxa, 2016)
The subfamily Cylapinae (Insecta, Heteroptera: Miridae) from India is reviewed. Three tribes, seven genera and nineteen species are cited from the country, keyed and described. Six species are described as new: Fulvius kadapaensis sp. nov., Peritropis kodava sp. nov., Peritropis pathaki sp. nov., Peritropis sangai sp. nov., Peritropis yasunagai sp. nov. and Rhinomiris prathapani sp. nov. A new synonymy is published: Peritropis lewisi (Distant, 1904) (valid name) = Peritropis indicus Gorczyca, 2006b (new junior subjective synonym).